(untitled) (Research, Society and Development, 2022)
Environmental issues are increasingly being discussed and debated in our society, whether in the private sphere, where companies are increasingly seeking sustainable solutions and even between nations through international cooperation agreements, such as reducing pollutants. The fact is that society is trying these practices and has demanded from companies and government attitudes and policies aligned with global issues that require a joint effort in terms of minimizing waste, saving natural resources, improving quality, diversifying the energy matrix among many others actions. In this context, civil construction appears as a storehouse of opportunities on the other hand, it needs investments in new technologies, and inspection in compliance with current legislation and good market practices. The objective of this work is to identify sustainability present in civil construction, under the view of professionals, in order to evaluate the tools and good practices used in the works. The methodology used is based on a bibliographic study through academic works in order to substantiate the study, as well as field research with market professionals at the most different levels and positions.